1998
DOI: 10.1016/s0022-5347(01)64016-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Retrovesical and Extrarenal Retroperitoneal Hydatidosis: Clinical Study of 10 Cases and Literature Review

Abstract: An isolated retrovesical, retroperitoneal or even retrocrural cyst can be the unique manifestation of hydatid disease. Although difficult, preoperative diagnosis is desirable for the selection of a surgical approach and prevention of allergic reactions and operative spillage. A diagnostic algorithm and several therapeutic guidelines are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 18 publications
2
71
0
2
Order By: Relevance
“…Hastalığın yaygın-lığı konusundaki verilerin yetersiz olduğu, bu verilerin çoğunlukla hastane kayıtlarına ait bilgileri içerdiği kaydedilmektedir (11,12 Enfeksiyonun cinsiyetler arasındaki dağılımları, yapılan çalışmala-ra göre farklılık göstermekte, bazı çalışmalarda kadınlarda (17,18,20,32,42,43), bazı çalışmalarda ise erkeklerde daha sık görüldüğü kaydedilmektedir (12,44). Bu farklılığın, kişilerin için-de yaşadıkları çevre ile olan ilişkilerine, sosyal hayatın kadın-erkek sorumluğundaki farklılıklarına ve köpekle olan yakın temasa göre değiştiği, istatistiksel olarak anlamlı olmamakla birlikte, genel olarak kadınlarda daha sık görüldüğü bildirilmektedir (32).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Hastalığın yaygın-lığı konusundaki verilerin yetersiz olduğu, bu verilerin çoğunlukla hastane kayıtlarına ait bilgileri içerdiği kaydedilmektedir (11,12 Enfeksiyonun cinsiyetler arasındaki dağılımları, yapılan çalışmala-ra göre farklılık göstermekte, bazı çalışmalarda kadınlarda (17,18,20,32,42,43), bazı çalışmalarda ise erkeklerde daha sık görüldüğü kaydedilmektedir (12,44). Bu farklılığın, kişilerin için-de yaşadıkları çevre ile olan ilişkilerine, sosyal hayatın kadın-erkek sorumluğundaki farklılıklarına ve köpekle olan yakın temasa göre değiştiği, istatistiksel olarak anlamlı olmamakla birlikte, genel olarak kadınlarda daha sık görüldüğü bildirilmektedir (32).…”
Section: Discussionunclassified
“…Bu farklılığın, kişilerin için-de yaşadıkları çevre ile olan ilişkilerine, sosyal hayatın kadın-erkek sorumluğundaki farklılıklarına ve köpekle olan yakın temasa göre değiştiği, istatistiksel olarak anlamlı olmamakla birlikte, genel olarak kadınlarda daha sık görüldüğü bildirilmektedir (32). Bu çalışmada, olguların %52,94'ünü erkek hastalar, %47,05'ini kadın hastalar oluşturmuş, bu sonuç daha önce yapılan çalışma-lar ile (12,44) uyumlu bulunmuştur.…”
Section: Discussionunclassified
“…(3) Retrovesical hydatid cysts may have varied and nonspecific presentation. In the series by Angulo et al (3) the most common presentation was a palpable mass followed by flank pain, LUTS, urinary retention and dysuria.…”
Section: Discussionmentioning
confidence: 99%
“…Reported symptoms associated with the bladder include urinary frequency, urgency, retention and pain on micturation. 7,8 In a recent review of the previously reported cases with seminal vesicle hydatidosis, symptomatology included dysuria, colic and hydatiduria, 3 difficulty and a sense of burning during urination, 4 frequency and acute urinary retention. 5 Syncope is the presenting symptom of the currently presented case and there were no other complaints related to the genitourinary system.…”
Section: Discussionmentioning
confidence: 99%